HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN PENYESUAIAN DIRI PADA REMAJA AWAL DI PANTI ASUHAN KOTA DENPASAR - Tricahyani, Ida Ayu Ratih; Widiasavitri, Putu Nugrahaeni (Jurnal Psikologi Udayana, 2016)
Early adolescence is a transition from childhood to adulthood. In this period, early adolescence experienced many changes both physically and psychologically. Same with the case of early adolescents who lived in the orphanage, besides the fulfillment of physiological, early adolescents in the orphanage also need a healthy psychological development, one of them is the process of personal adjustment. Personal sdjustment aiming to get harmony between the demands of the self and the environment in which the individual resides. Personal  adjustment is a form of behavior that is intended to respond to the needs that exist within the individual. In order to get a good adjustment in early adolescents orphanage, it needs social support. Social support refers to the provision of comfort, care and respect. This study aimed to determine the relationship between social support and personal adjustment to early adolescents orphanage in Denpasar.This research is a quantitative method with simple regression analysis. Subjects in this study are early adolescents orphanages in Denpasar, age range is 12 to 17 years. Sample of this study is 100 persons. The sampling method using simple random sampling. Data is collected through social support scale and the scale of the adjustment of early adolescence in the orphanage. Social support scale reliability is 0.735 and the reliability of scale adjustment in early adolescence in the orphanage is 0.744. The research data shows a normal distribution and linear. The results of this research shows the correlation coefficient is 0.558 with a significance at 0.000 (p <0.05). It means that there is a positive relationship between social support and personal adjustment in early adolescents orphanage. Contribution of social support to the personal adjustment in early adolescents orphanage is 31,2%.   Key words : social support, personal adjustment, early adolescents, orphanage